Graduación y deserción en la escuela de matemática de la UNA Cohortes 1995 a 1998 - Chaves Esquivel, Edwin (Uniciencia, 2003)
The efficiency of the graduation processes and the time spent at the university have a special importance with regard to both the accreditation processes of the different academic programs that train specialist in the country as well as the lack of economic resources assigned to education. The methodology used appears to be very effective in this kind of analysis. It not only allows one to evaluate the main statistical tests but also to analyze student desertion in these processes. For this academic program the results are discouraging, since less than 30% of incoming students actually complete a university degree. Moreover, only 12% of the students obtain a Bachelor degree. These data should encourage the people in charge of these academic programs to evaluate their institution, since these percentages of student desertions are too high. However students take an average of 4 or 5 years to obtain the “Profesorado” or Bachelor. In this regard the program is successful because the time spent is low compared to degrees conferred in other programs at public universities in Costa Rica.